Mixed finite element for modelling interfaces - Bouziane, Salah; Bouzerd, Hamoudi; Guenfoud, Mohamed (European Journal of Computational Mechanics, 2009)
A special finite element based on Reissner’s mixed variational principle has been presented to model interface between two materials. The present element is a 7-node two dimensional mixed finite element with 5 displacement nodes and 2 stress nodes. The mixed interface finite element ensures the continuity of stress and displacement vectors at the interface on the coherent part and the discontinuity of this one on the cracked part. This element has been formulated starting from a parent element in a natural plane with an aim of modelling different types of interfaces with various orientations. This work is essentially devoted to the formulation of the interface element and the study of convergence and validation of this element. Results obtained from the present mixed interface element have been shown to be in good agreement with the analytical solutions.